Women in the Palm Oil Industry in Social-Environmental Power Relations: Media Narratives and Women’s Agency in the Wetlands of Riau - Chelsy Yesicha; Samsir Samsir; Yasir Yasir; Andri Sulistyani; Sesdia Angela (Universitas Telkom, 2026)
The palm oil industry is a strategic sector in Indonesia's economic development, but its expansion has also given rise to various ecological and social problems, particularly related to gender inequality in labor relations and natural resource management. In public discourse, narratives of palm oil development often portray women as part of economic success, but at the same time their experiences and voices are often marginalized. This phenomenon shows a battle of discourse between the dominant economic development narrative and the social experiences of women in plantation communities. This study aims to analyze how the discourse on women in the palm oil industry is represented in digital media and how women in palm oil interpret and negotiate their experiences in the context of social and ecological sustainability. The study uses a qualitative approach with Norman Fairclough's Critical Discourse Analysis method combined with an ecofeminist perspective. Primary data was obtained through the analysis of three YouTube documentary videos featuring the lives of female palm oil workers and in-depth interviews with 15 women in the Riau wetland area, namely Kampar, Bengkalis, and Siak. The results show that media representations shape an arena of discourse between the ideologies of industrial capitalism, liberal feminism, and critical ecofeminism. The media often depicts women as productive workers and symbols of resilience, but tends to obscure the structures of exploitation and ecological inequality in the palm oil industry. On the other hand, the experiences of women at the local level show the emergence of critical awareness and social practices that negotiate the relationship between gender, plantation economics, and environmental sustainability. These findings confirm that palm oil women are not only objects of development, but also actors who construct counter-narratives for social and ecological justice in the palm oil industry.